2012
DOI: 10.1186/1756-3305-5-21
|View full text |Cite
|
Sign up to set email alerts
|

Low and seasonal malaria transmission in the middle Senegal River basin: identification and characteristics of Anopheles vectors

Abstract: BackgroundDuring the last decades two dams were constructed along the Senegal River. These intensified the practice of agriculture along the river valley basin. We conducted a study to assess malaria vector diversity, dynamics and malaria transmission in the area.MethodsA cross-sectional entomological study was performed in September 2008 in 20 villages of the middle Senegal River valley to evaluate the variations of Anopheles density according to local environment. A longitudinal study was performed, from Oct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 35 publications
4
44
0
Order By: Relevance
“…It has been reported before that kdr allele frequencies can vary seasonally, and in our data, samples were pooled for an entire year. 19,62,63 We also have shown that selection has acted strongly on this locus after the application of pyrethroid insecticides.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported before that kdr allele frequencies can vary seasonally, and in our data, samples were pooled for an entire year. 19,62,63 We also have shown that selection has acted strongly on this locus after the application of pyrethroid insecticides.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, pockets of individuals displaying a greater tolerance for desiccation may also be able to persist through the dry season; and indeed, this seems to be the case, especially given the seasonality of malaria in some areas (e.g. Patz et al, 1998;Charlwood et al, 2000;Tanser et al, 2003;Ndiath et al, 2012).…”
Section: Research Articlementioning
confidence: 99%
“…This is consistent with the earlier study in Senegal ( Ndiath et al , 2011) but differs from a recent survey conducted in Mali ( Fryxell et al , 2012). The study site in Senegal located in the village of Dielmo (13°43'N, 16°24'W) ( Ndiath et al , 2012)) was geographically closer (200km) than Mali sites (>800km) to our collection sites in Guinea-Bissau. The Senegal study site at Dielmo and nine of our study sites were proximal (<50km) to the Atlantic Ocean, while Mali is a land-locked country at least 500km away from the Atlantic Ocean.…”
Section: Resultsmentioning
confidence: 87%
“…Very low infection rates and absence of malarial parasites, traditionally found in West and Central African populations of A. pharoensis has always led to the conclusion that this mosquito plays little role in malaria transmission despite its anthropophilic habits and that it can be easily experimentally infected ( DeMeillon, 1947; Ndiath et al , 2012; Tchouassi et al , 2012). In drier Sahel regions of Africa where the major vectors of malaria are absent or very rare and irrigated rice and other crop lands are increasing, A. pharoensis is considered more important at maintaining low levels of malaria ( Kerah-Hinzoumbe et al , 2009; Kibret et al , 2010).…”
Section: Resultsmentioning
confidence: 99%